Octaethyl vs Tetrabenzo Functionalized Ru Porphyrins on Ag(111): Molecular Conformation, Self-Assembly and Electronic Structure - Meier, Dennis; Knecht, Peter; Vezzoni Vicente, Pablo; Eratam, Fulden; Xu, Hongxiang; Lee, Tien-Lin; Generalov, Alexander; Riss, Alexander; Yang, Biao; Allegretti, Francesco; Feulner, Peter; Reichert, Joachim; et al. (Journal of Physical Chemistry C, 2025)
Metalloporphyrins on interfaces offer a rich playground for functional materials and hence have been subjected to intense scrutiny over the past decades. As the same porphyrin macrocycle on the same surface may exhibit vastly different physicochemical properties depending on the metal center and its substituents, it is vital to have a thorough structural and chemical characterization of such systems. Here, we explore the distinctions arising from coverage and macrocycle substituents on the closely related ruthenium octaethyl porphyrin and ruthenium tetrabenzo porphyrin on Ag(111). Our investigation employs a multitechnique approach in ultrahigh vacuum, combining scanning tunneling microscopy, low-energy electron diffraction, photoelectron spectroscopy, normal incidence X-ray standing wave, and near-edge X-ray absorption fine structure, supported by density functional theory. This methodology allows for a thorough examination of the nuanced differences in the self-assembly, substrate modification, molecular conformation and adsorption height.Metalloporphyrins on interfaces offer a rich playground for functional materials and hence have been subjected to intense scrutiny over the past decades. As the same porphyrin macrocycle on the same surface may exhibit vastly different physicochemical properties depending on the metal center and its substituents, it is vital to have a thorough structural and chemical characterization of such systems. Here, we explore the distinctions arising from coverage and macrocycle substituents on the closely related ruthenium octaethyl porphyrin and ruthenium tetrabenzo porphyrin on Ag(111). Our investigation employs a multitechnique approach in ultrahigh vacuum, combining scanning tunneling microscopy, low-energy electron diffraction, photoelectron spectroscopy, normal incidence X-ray standing wave, and near-edge X-ray absorption fine structure, supported by density functional theory. This methodology allows for a thorough examination of the nuanced differences in the self-assembly, substrate modification, molecular conformation and adsorption height.